THE INFLUENCE OF E-WOM, PERCEIVED QUALITY AND PRICE ON PURCHASE DECISIONS WITH BRAND IMAGE AS AN INTERVENING VARIABLE (Study on The Body Shop Consumers in Semarang City) - Rizqia Intan Afrianti (Diponegoro Journal of Management, 2026)
The cosmetics and body care industry is experiencing rapid development as consumer awareness of skin health, environmental sustainability, and clean beauty trends increases. This condition encourages increasingly fierce competition between cosmetics brands, including for The Body Shop, which is known as a brand based on ethical values and sustainability. Although it remains one of the market leaders, The Body Shop's sales data in Indonesia shows a downward trend from 2021 to 2024. This decline indicates a change in consumer behavior and an increasing influence of other factors in the purchase decision-making process, such as electronic word of mouth (E-WOM), perceived quality, and price.This study aims to analyze the influence of E-WOM, perceived quality, and price on purchase decisions with brand image as an intervening variable in consumers of The Body Shop in Semarang City. This study uses a quantitative approach with a survey method through the distribution of questionnaires to 240 respondents who have used The Body Shop product. The data analysis technique used is Structural Equation Modelling (SEM) with the help of the AMOS program version 29.0.The results of the study show that E-WOM, perceived quality, and price have a positive effect on brand image. In addition, E-WOM, perceived quality, and price also have a positive effect on purchase decisions. The findings of this study show that consumer perception of product quality, information from other consumers in digital media, and price suitability have an important role in shaping brand image and driving purchase decisions. A strong brand image has also been proven to strengthen the relationship between these factors and consumer purchasing decisions.